HAK ULAYAT MASYARAKAT ADAT SUKU AWYU DI KABUPATEN BOVEN DIGOEL - Arman, Nada; Revi, Semepa; Arman, Adithia Nanda Fadilla (Animha Law Journal, 2024)
Customary rights are an important aspect in the lives of indigenous peoples, especially for the Awyu Tribe in Boven Digoel Regency, South Papua. This right reflects the close relationship between indigenous peoples and land as a source of life and cultural identity. The research results show that the customary rights of the Awyu Tribe are regulated based on customary law passed down from generation to generation. Customary land not only has economic value but also spiritual and social value for the community. However, the existence of these customary rights often faces challenges, such as conflicts with the interests of outside parties, including plantation and mining companies, as well as a lack of formal recognition by the government. Apart from that, social changes and modernization have also influenced indigenous peoples' understanding of their traditional values.